SIMULASI DAN UJI KINERJA ALGORITMA JOHNSON UNTUK PENENTUAN RUTE TERBAIK PADA JARINGAN SOFTWARE DEFINED NETWORK - Ilhamsyah, Muhammad; Mangkudjaja, Rumani; Hertiana, Sofia Naning (Jurnal Sistem Komputer, 2016)
Since the development of computer network technology is larger and more complex, computer network technology which is more flexible and easier to configure is now required. SDN (Software Defined Network) is one of the solutions for the computer network requirement which is now larger and more complex. SDN offers the network concept which is different from the traditional network. In the traditional network, control plane and data plane are in one device; it is different from the concept offered by SDN in which control plane and data plane are designed separately on SDN. SDN concept has simplified the existing network concept since the network control on a controller is programmable and it makes the network easy to configure and more flexible. In this research, the researcher applied the routing service using the shortest path-searching method of Johnson algorithm on SDN network and analyzed the network performance. The implementation of Johnson algorithm was used on the network created on mininet emulator. The OpenFlow protocol will be used on this network. The result of performance test on SDN network in which the routing service has been applied with Johnson algorithm shows that the larger the network, the more time required for convergence; routing is flexible since it can adapt to the change on network.